Influence of fin configurations in the heat transfer effectiveness of Solid solid PCM based thermal control module for satellite avionics: Numerical simulations. (June 2020) - Raj, Cyril Reuben; Suresh, S.; Bhavsar, R.R.; Singh, Vivek Kumar; Govind, K. Akash
Highlights: Numerical study on fin effectiveness with SS-PCM for better thermal control module. Taguchi optimization and validation by ANOVA, predicts the sustainability of fins. Taguchi integrated numerical heat transfer simulation under orbital conditions. Square fins have better thermal control of 1.3 & 0.5 K under geometrical constraints. Triangular fins have mass reduction of 25 and 35% with significant thermal control. Abstract: This paper reports the influence of fin configurations in a SS-PCM based thermal control module. The materials considered are Layered perovskite as SS-PCM and Aluminium for the heat sink. Taguchi optimization integrated numerical simulations are carried out to study the effect of fin shape, fin thickness, base thickness and total number of fins for a constant heat flux of 10W at 1200s "on", 4800s "off" duty cycles of an avionic component under orbital conditions. The ANOVA results determined the contribution factor of each parameter. For a fixed geometry, simulation results exhibit better heat transfer in square straight fin configuration and achieved a lower heat sink base temperature of 1.3 and 0.5K than the circular and triangular straight fin configuration, which also proves to be in good agreement with the aspect ratio of the fins. However, triangular fins performed better and had a mass reduction of 25% and 35% than square and circular counterparts at constant volume fraction, leading to substantial cost savings. Also, the tapered fin configurations were more effective in reducing the base temperature by 0.6K and thereby enhancing faster heat transfer than their straight counterparts. In conclusion, the tapered triangular fin configuration is suitable for SS-PCM based thermal control module for satellite avionics. Graphical abstract: Image, graphical abstract